Răspuns :
Salut,
(2x-1)²-2(x+4) = (2x+1)²+3(x+2)-1
4x²-4x+1-2x-8 = 4x²+4x+1+3x+6-1
4x²-6x-7 = 4x²+7x+6
-6x-7x = 6+7
-13x = 13
x = 13/-13
x = -1.
Succes! :3
(2x-1)²-2(x+4) = (2x+1)²+3(x+2)-1
4x²-4x+1-2x-8 = 4x²+4x+1+3x+6-1
4x²-6x-7 = 4x²+7x+6
-6x-7x = 6+7
-13x = 13
x = 13/-13
x = -1.
Succes! :3
(2x-1)^2-2(x+4)=(2x+1)^2+3(x+2)-1
4x^2 - 4x + 1 - 2x - 8 = 4x^2 +4x + 1 + 3x +6 - 1
4x^2 - 6x - 7 = 4x^2 +7x + 6
4x^2 - 6x - 4x^2 - 7x = 6 +7
- 13x = 13
x = 13 : - 13
x = - 1
4x^2 - 4x + 1 - 2x - 8 = 4x^2 +4x + 1 + 3x +6 - 1
4x^2 - 6x - 7 = 4x^2 +7x + 6
4x^2 - 6x - 4x^2 - 7x = 6 +7
- 13x = 13
x = 13 : - 13
x = - 1